2014
DOI: 10.1900/rds.2014.11.167
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Potential of Milk Thistle in Diabetes

Abstract: ■ AbstractMilk thistle has been known for more than 2.000 years as a herbal remedy for a variety of disorders. It has mainly been used to treat liver and gallbladder diseases. Silibum marianum, the Latin term for the plant, and its seeds contain a whole family of natural compounds, called flavonolignans. Silimarin is a dry mixture of these compounds; it is extracted after processing with ethanol, methanol, and acetone. Silimarin contains mainly silibin A, silibin B, taxifolin, isosilibin A, isosilibin B, silic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 41 publications
1
40
0
Order By: Relevance
“…Some flavonoids such as rutin, quercetin (Figure 2A), isoorientin, 3-caffeoylquinic acid (chlorogenic acid), and silibin isoform 3 (obtained of milk thistle) have hypoglycemic properties [63][64][65][66][67].…”
Section: Flavonoidsmentioning
confidence: 99%
“…Some flavonoids such as rutin, quercetin (Figure 2A), isoorientin, 3-caffeoylquinic acid (chlorogenic acid), and silibin isoform 3 (obtained of milk thistle) have hypoglycemic properties [63][64][65][66][67].…”
Section: Flavonoidsmentioning
confidence: 99%
“…Although silymarin has mainly been used to treat liver diseases [143], its antidiabetic activity was recently reported and is associated with an anti-glycation profile [144,145], inhibition of aldose reductase [143], partial agonist activity in peroxisome proliferator-activated receptor γ (PPARγ) [143], antioxidant capacity and radical scavenging [144,146]. All these characteristics make silymarin an interesting candidate for the prevention and treatment of diabetic complications, which has recently been demonstrated both in experimental models and in humans (the same as for quercetin and resveratrol).…”
Section: Potential Of Natural Products With Antioxidant Effects Fomentioning
confidence: 99%
“…4,5 A literature review revealed that various antioxidants were used in diabetes-associated nephrotoxicity and neurotoxicity. 6,7 In addition, antioxidant agents were used in many studies with cisplatin-, vancomycin-, aminoglycoside-, and acoustic-trauma-induced ototoxicity. However, studies on agents for cochlear damage due to diabetes were inadequate.…”
Section: Introductionmentioning
confidence: 99%